Relationship Between Stress Level and Hopelessnes among Adolescents Victim of Bullying - Purnama, Heni; Zalsabila, Rezkya (STIKep PPNI Jawa Barat, 2023)
Aims: Bullying is a serious problem faced by teenagers nowadays. The impact of bullying could make victims feel insecure and away from their social life. Objective: This study aims to determine the relationship between stress level and feelings of hopelessness among adolescents victim of bullying. Methods: This research was a descriptive correlative study with a cross sectional study approach. Simple random sampling was applied to choose the class, the inclusion criteria was student who had experienced as a victim of bullying. A total of 489 senior high school students participated as respondents. Sample were taken by using a simple random sampling technique. The instruments used the Beck Hopelessness Scale and the Perceived Stress Scale (PSS-10). Spearman Rank Correlation was used as data analysis in this study. Results: Most of the respondents were female (84%), with an average age of 16 years. More than half of the total respondents had severe of hopelessness (57.9%). The mean score of the stress level experienced by the respondents was 23.21 (±SD 4.427). The results of the bivariate analysis showed that stress levels had a relationship with hopelessness among adolescents victim of bullying (p-value=0.00). Conclusion: The level of stress was a factor that contributes to the hopelessness of adolescent victims of bullying.. Suggestion: School should develop an intervention program that can prevent stress and overcome hopelessness in adolescents victims of bullying.